2013
DOI: 10.4141/cjps2013-052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synthetic and organic herbicides applied banded for weed control in carrots (Daucus carota L.)

Abstract: Main, D. C., Sanderson, K. R., Fillmore, S. A. E. and Ivany, J. A. 2013. Comparison of synthetic and organic herbicides applied banded for weed control in carrots ( Daucus carota L.). Can. J. Plant Sci. 93: 857–861. The necessity to reduce environmental impact and control the increasing cost of production has many carrot growers seeking new methods of crop management. This research evaluated the potential of applying herbicides in 30-cm bands over the carrot row in combination with between-the-row cultivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The reduction of herbicide use achieved with T1 and T2 spraying systems is relevant (50 and 66% respectively) and therefore it reduces the risk of environmental contamination. The herbicide use reduction with the adoption of band application is in keeping with previous studies on various crops [13,17,18] and it is clearly related to the percentage of the field sprayed. A further herbicide reduction could be reached by decreasing the width of the treated band along the crop row.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reduction of herbicide use achieved with T1 and T2 spraying systems is relevant (50 and 66% respectively) and therefore it reduces the risk of environmental contamination. The herbicide use reduction with the adoption of band application is in keeping with previous studies on various crops [13,17,18] and it is clearly related to the percentage of the field sprayed. A further herbicide reduction could be reached by decreasing the width of the treated band along the crop row.…”
Section: Discussionsupporting
confidence: 85%
“…An important reduction in the amount of herbicides used, and consequently a notable decrease of the risks of herbicide contamination in water bodies, can therefore be achieved by switching from broadcast application to band application along the crop row combined with inter-row mechanical control. Similar strategies with pre-emergence or post-emergence herbicide application for crops, such as maize, soybean, sunflower [13][14][15][16], but also carrots [17], potatoes [18] and sugar beet [19] gave similar levels of weed control and crop yields to the corresponding strategies based on broadcast herbicide application, but with relevant reduction of herbicide use.…”
Section: Introductionmentioning
confidence: 88%
“…Achieving yields at high levels with an appropriate weed control and reducing herbicide consumption is the subject of many studies [17,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The TFI of CON averaged by farms and years was 1 in Italy and 2 in Hungary, whereas for IWM, this was reduced to 0.5 and 1.2 respectively. Previous research has shown that band spraying of herbicides is as effective for weed control as conventional applications in different cropping systems, with herbicide savings of up to 50% in maize and soybean (Pannacci & Tei, ), 66% in carrot and potato crops (Ivany, ; Main et al ., ) and up to 70% in sugar beet (Wiltshire et al ., ).…”
Section: Discussionmentioning
confidence: 99%